ANALISIS FAKTOR MAKROEKONOMI YANG MEMPENGARUHI PROFITABILITAS BANK (STUDI PADA PT. BANK RAKYAT INDONESIA (PERSERO) TBK.) - Indahsari, Silvya Nur; Hascaryani, Tyas Danarti (Jurnal Ilmiah Mahasiswa FEB, 2014)
This research aims to find out the effect of BI Rate, exchange rate, and money supply on bank’s profitability especially PT. Bank Rakyat Indonesia (Persero) Tbk. The most important indicator in evaluating the bank’s profitability is Return On Asset (ROA). Multiple linear regression is used to analyze this data research. The results showed that increase of BI Rate push bank’s profitability to rise, appreciation of the exchange rate has effect on increasing bank’s profitability, and increase in the money supply is proven to increase bank’s profitability.   Keyword : Return On Asset (ROA), BI Rate, exchange rate, money supply.